2015
DOI: 10.1038/pcan.2015.52
|View full text |Cite
|
Sign up to set email alerts
|

Atypical small acinar proliferation (ASAP): Is a repeat biopsy necessary ASAP? A multi-institutional review

Abstract: Although 34% of patients with an initial diagnosis of ASAP who had repeat biopsy were subsequently diagnosed with PCa only, only 22% (8% of the total cohort) were found to have high-grade disease. Higher PSA was associated with increased risk of identifying PCa on repeat biopsy. These findings suggest that immediate repeat biopsy may be omitted in the majority of men with ASAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 27 publications
0
31
1
1
Order By: Relevance
“…For example, the recent ProtecT trial provides strong level I evidence regarding the safety and efficacy of active surveillance by demonstrating equivalent overall survival and cancer-specific survival when compared to management with either surgery or radiotherapy 11,17 . Reasonably, such patients may be best managed in accordance with current active surveillance guidelines to minimize the overutilization of prostate biopsies 9 . Moreover, one can consider further investigation with newer imaging modalities such as multi-parametric magnetic resonance imaging 18,19 or employ a less morbid transperineal template-guided approach on repeat biopsy 20 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the recent ProtecT trial provides strong level I evidence regarding the safety and efficacy of active surveillance by demonstrating equivalent overall survival and cancer-specific survival when compared to management with either surgery or radiotherapy 11,17 . Reasonably, such patients may be best managed in accordance with current active surveillance guidelines to minimize the overutilization of prostate biopsies 9 . Moreover, one can consider further investigation with newer imaging modalities such as multi-parametric magnetic resonance imaging 18,19 or employ a less morbid transperineal template-guided approach on repeat biopsy 20 .…”
Section: Discussionmentioning
confidence: 99%
“…First, it reaffirms the rate of progression of clinically significant prostate cancer on repeat biopsy of approximately 10% 10,16,18,21 . In a multi-institutional review, Leone, et al 9 reported that on repeat biopsy 34% were diagnosed with prostate cancer; however, 8% had Gleason ≥7 disease. Consistent with these findings, Tosoian, et al 18 demonstrated 5% of patients with ASAP were diagnosed with Gleason ≥7 disease using magnetic resonance imaging/TRUS fusion-guided for repeat biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…В исследованиях отмечается, что атипическая мелко ацинарная пролиферация (АМАП) встречается у 5 % пациентов, которым выполнена биопсия ПЖ [4,5]. Изолированные комплексы АМАП -известный доказанный предиктор РПЖ.…”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified